1990
DOI: 10.1086/646085
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Risk for Falls by Clinical Department: Implications for Prevention

Abstract: To examine rates of falls and injuries by clinical department, a retrospective analysis was performed of 874 inpatient falls during a one-year period in a 1,000-bed acute-care hospital. Incident reports were reviewed, and for those patients injured, medical records were abstracted. Fall rates were calculated by age, sex and service using total patient days as the denominator. During 1983, 874 falls occurred during 282,713 adult patient days (31/10(4) days). Fall rates were significantly higher (odds ratio = 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 7 publications
1
11
0
1
Order By: Relevance
“…M uch research has been conducted in the hospital setting to reduce falls and prevent serious injury (Chu et al, 1999;Fischer et al, 2005;Hendrich, Nyhuis, Kippenbrock, & Soja, 1995;Hitcho et al, 2004;Krauss et al, 2005Krauss et al, , 2007Lakatos et al, 2009;McCarter-Bayer, Bayer, & Hall, 2005;Morgan, Mathison, Rice, & Clemmer, 1985;O'Connell, Baker, Gaskin, & Hawkins, 2007;O'Connell, Cockayne, Wellman, & Baker, 2005;Pautex, Hermann, & Zulian, 2008;Rhode, Myers, & Vlahov, 1990;Stevenson, Mills, Welin, & Beal, 1998), as falls are commonly reported in hospitals (Institute for Healthcare Improvement, n.d.). M uch research has been conducted in the hospital setting to reduce falls and prevent serious injury (Chu et al, 1999;Fischer et al, 2005;Hendrich, Nyhuis, Kippenbrock, & Soja, 1995;Hitcho et al, 2004;Krauss et al, 2005Krauss et al, , 2007Lakatos et al, 2009;McCarter-Bayer, Bayer, & Hall, 2005;Morgan, Mathison, Rice, & Clemmer, 1985;O'Connell, Baker, Gaskin, & Hawkins, 2007;O'Connell, Cockayne, Wellman, & Baker, 2005;Pautex, Hermann, & Zulian, 2008;Rhode, Myers, & Vlahov, 1990;Stevenson, Mills, Welin, & Beal, 1998), as falls are commonly reported in hospitals (Institute for Healthcare Improvement, n.d.).…”
Section: At a Glancementioning
confidence: 99%
See 2 more Smart Citations
“…M uch research has been conducted in the hospital setting to reduce falls and prevent serious injury (Chu et al, 1999;Fischer et al, 2005;Hendrich, Nyhuis, Kippenbrock, & Soja, 1995;Hitcho et al, 2004;Krauss et al, 2005Krauss et al, , 2007Lakatos et al, 2009;McCarter-Bayer, Bayer, & Hall, 2005;Morgan, Mathison, Rice, & Clemmer, 1985;O'Connell, Baker, Gaskin, & Hawkins, 2007;O'Connell, Cockayne, Wellman, & Baker, 2005;Pautex, Hermann, & Zulian, 2008;Rhode, Myers, & Vlahov, 1990;Stevenson, Mills, Welin, & Beal, 1998), as falls are commonly reported in hospitals (Institute for Healthcare Improvement, n.d.). M uch research has been conducted in the hospital setting to reduce falls and prevent serious injury (Chu et al, 1999;Fischer et al, 2005;Hendrich, Nyhuis, Kippenbrock, & Soja, 1995;Hitcho et al, 2004;Krauss et al, 2005Krauss et al, , 2007Lakatos et al, 2009;McCarter-Bayer, Bayer, & Hall, 2005;Morgan, Mathison, Rice, & Clemmer, 1985;O'Connell, Baker, Gaskin, & Hawkins, 2007;O'Connell, Cockayne, Wellman, & Baker, 2005;Pautex, Hermann, & Zulian, 2008;Rhode, Myers, & Vlahov, 1990;Stevenson, Mills, Welin, & Beal, 1998), as falls are commonly reported in hospitals (Institute for Healthcare Improvement, n.d.).…”
Section: At a Glancementioning
confidence: 99%
“…The study did not provide additional descriptions of the falls. In a quantitative, retrospective analysis of hospital falls and injuries by clinical departments, Rhode et al (1990) found that the oncology department had 62 of 874 total falls over a one-year period. Compared to patients in six other hospital services (women and infants, surgery, cardiology, neurology and orthopedics, medicine, and psychiatry), the oncology service had the highest percentage of falls resulting in injury (43%).…”
Section: At a Glancementioning
confidence: 99%
See 1 more Smart Citation
“…Dentre as metas estabelecidas pelo PNSP, estão as estratégias para a redução dos incidentes de queda durante a hospitalização 3 . A Organização Mundial de Saúde (OMS) define queda como vir a inadvertidamente ficar no solo ou em outro nível inferior, excluindo mudanças de posições intencionais para se apoiar em móveis, paredes ou outros objetos 4 .…”
unclassified
“…3,4 Recently, the mortality in epilepsy monitoring units study (MORTEMUS) looked at 133,788 continuous vEEG studies in 147 EMUs across Israel, Europe, Australia, and New Zealand, and examined the incidence of sudden unexpected death in epilepsy (SUDEP) in EMUs. Rather than trying to alleviate symptoms through the initiation of treatment, symptoms in EMUs are triggered through treatment withdrawal (antiseizure medications) and activation methods (i.e., sleep deprivation and hyperventilation).…”
mentioning
confidence: 99%